La aplicación del numeral 1 del artículo 665 del COIP, frente al principio de oralidad contemplado en el artículo 168 numeral 6 de la constitución ecuatoriana. - Narváez Calderón, Daysi Geoconda (2017)
Once the problem and object of study were investigated, it was evident that there were no similar works to the one I am proposing. For the purpose of this research, I conducted an analysis of the legal contradiction that exists in Article 665, paragraph 1* of the COIP (Spanish Constitutional Court), regarding the principle of oral communication contemplated in Article 168, paragraph 6* of the Constitution, as well as in International Treaties and Conventions. However, it was necessary to thoroughly investigate the problem I am presenting. For this reason, it was not possible to find degree theses, theses, scientific articles, or other projects on the subject in the local and virtual libraries of the Universidad Regional Autónoma de los Andes, Uniandes-Tulcán, or in other extension and parent libraries, that expressly address this topic, which has been dragging on since previous constitutions and regulations. Furthermore, I have investigated the repositories of the country's universities, where none exist either. I have presented a topic from the perspective and proposal I have formulated, so it is of great importance and significance to conduct an in-depth analysis of this subject of study, which will allow me to provide the reader with an excellent work.